Методы нормализации статического геомагнитного поля в жилых домах - Розов, В.Ю.; Завальный, А.В.; Золотов, С.М.; Грецких, С.В. (Електротехніка і електромеханіка, 2015)
Показана необходимость нормализации до безопасных значений индукции статического геомагнитного поля (ГМП) в
помещениях высотных каркасно-монолитных жилых домов, массивные ферромагнитные несущие конструкции которых значительно (на 50%) ослабляют естественное ГМП. Теоретически и экспериментально обоснованы методы
нормализации ГМП, реализуемые без применения дополнительных экранирующих элементов. Разработаны рекомендации по проектированию и строительству «магниточистых» жилых домов с комфортными условиями проживания
по статическому геомагнитному полю. Показана необхідність нормалізації до безпечних значень індукції статичного геомагнітного поля (ГМП) у приміщеннях
висотних каркасно-монолітних житлових будинків, масивні феромагнітні несучі конструкції яких значно (на 50%) послаблюють природне ГМП. Теоретично і експериментально обґрунтовані методи нормалізації ГМП, що реалізуються
без застосування додаткових екрануючих елементів. Розроблено рекомендації з проектування та будівництва «магніточистих» житлових будинків з комфортними умовами проживання за статичним геомагнітним полем. In the paper, we show the necessity of normalization of the static
geomagnetic field (GMF) inside high-rise frame-monolithic
houses to safe values (90% of the natural rate at least). Massive
ferromagnetic construction of these buildings significantly (up
to 50 %) weakens the natural GMF. The normalization methods
are based on mathematical modeling of GMF in a residential
area. Simplified physical models of reinforced concrete building
structures are developed and used. The results of experimental
studies are also used in the framework of the development of the
methods. The following methods of normalization of GMF are
presented and justified: 1) the use of special steel with a relative
permeability less than 70 in housing construction; 2) restrictions on the use of long steel elements with the elongation coefficient in the critical range of 4<b<28; 3) demagnetization of
steel reinforcement before installing; 4) preventing the magnetization of steel reinforcement in the construction process. Practical recommendations for the design of «magnetic clean» houses
with comfortable living conditions in connection to the GMF are
proposed.